Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material and preparation method thereof, and hydrogen sensor and preparation method thereof
By using Au-loaded ZnO/Zn2SnO4/SnO2 composite sensitive materials, the existing hydrogen sensors have been solved, and a hydrogen sensor with high sensitivity and good repeatability for hydrogen detection at low temperatures is realized.
Patent Information
- Application Number
- CN202411745621.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
The existing single oxide semiconductor hydrogen sensors have problems such as slow response speed, high operating temperature and poor selectivity, which is difficult to meet the needs of improving the performance of semiconductor gas sensors.
Au-loaded ZnO/Zn2SnO4/SnO2 composite sensitive material is used to prepare Au-loaded ZnO-sensitive material with nanosheet assembly structure through hydrothermal reaction, and the composite sensitive material is formed by liquid deposition and annealing treatment to improve gas sensitivity performance.
A hydrogen sensor with high sensitivity, good repeatability and hydrogen selectivity for hydrogen detection at lower operating temperatures is realized, which is suitable for industrial production.
Smart Images

Figure CN119804574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensing and measurement technology, and in particular to an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material and a preparation method thereof, and a hydrogen sensor and a preparation method thereof. Background Art
[0002] Transformers are core components of power grid systems, and their operational performance directly impacts power supply reliability and quality. During operation, the insulating oil and organic insulating materials within transformers gradually age and decompose under the influence of heat and electricity over time, producing a variety of gases, primarily hydrogen, methane, acetylene, and carbon monoxide. By analyzing the relative amounts and formation rates of these characteristic gas components, it is possible to determine whether anomalies exist within the equipment and further infer the fault type and energy. Conventional methods for detecting dissolved gases in transformer oil include photoacoustic photospectroscopy, Raman spectroscopy, gas chromatography, Fourier transform infrared spectroscopy, and fiber Bragg grating (FBG) spectroscopy. These methods generally suffer from high costs, large errors, and complex maintenance. Semiconductor gas sensors offer significant advantages in sensitivity, cost, and integration. However, current single oxide semiconductor hydrogen sensors suffer from slow response, high operating temperatures, and poor selectivity. Therefore, heterojunction construction and noble metal modification can effectively improve the performance of semiconductor gas sensors. In particular, hydrogen sensors based on noble metal-loaded ZnO-based heterojunction sensitive materials remain under research and development. Summary of the Invention
[0003] The present invention aims to address the shortcomings of the existing single oxide semiconductor hydrogen sensor, which has slow response speed, high operating temperature, and poor selectivity, and the urgent need to improve the performance of semiconductor gas sensors. Thus, an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material and preparation method, as well as a hydrogen sensor and preparation method are proposed. The Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material of the present invention first prepares an Au-loaded ZnO sensitive material with a large specific surface area. The Au-loaded ZnO sensitive material is then treated with ammonium hexafluorostannate under acidic conditions provided by boric acid by liquid phase deposition and annealing to obtain an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material. The sensor prepared using the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material of the present invention has high sensitivity when detecting hydrogen, with the best sensitivity at 240°C, a low operating temperature, and a good response between 20 and 300 ppm. It also has good repeatability and hydrogen selectivity.
[0004] The first aspect of the present invention proposes a preparation method of an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, comprising: adding an Au-loaded ZnO sensitive material to a mixed solution containing boric acid and ammonium hexafluorostannate to carry out an ultrasonic reaction, performing solid-liquid separation on the ultrasonic reaction product, and drying and calcining the solid-phase product obtained by the solid-liquid separation to obtain an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material; the Au-loaded ZnO sensitive material is a hierarchical structure microsphere assembled from nanosheet layers.
[0005] Preferably, the preparation method of the Au-loaded ZnO sensitive material comprises: mixing hexamethylenetetramine, sodium citrate dihydrate, polyvinylpyrrolidone, hydrated tetrachloroauric acid, and water to form a first mixed solution; mixing sodium borohydride with water to form a second mixed solution; and mixing zinc nitrate hexahydrate with water to form a third mixed solution; mixing the first, second, and third mixed solutions and subjecting them to a hydrothermal reaction; washing and centrifuging the hydrothermal reaction product; and drying the solid phase product obtained by centrifugation to obtain the Au-loaded ZnO sensitive material. More preferably, the molar ratio of hydrated tetrachloroauric acid to zinc nitrate hexahydrate is 1 to 8:100. More preferably, the hydrothermal reaction conditions include a temperature of 80 to 150°C and a time of 2 to 6 hours; washing and centrifuging the hydrothermal reaction product; and drying the solid phase product obtained by centrifugation at a temperature of 60 to 90°C and a time of 8 to 12 hours.
[0006] Preferably, the mass ratio of the Au-loaded ZnO sensitive material, boric acid and ammonium hexafluorostannate is 1-2:1:8-10.
[0007] Preferably, the conditions for drying the solid phase product obtained by solid-liquid separation include: temperature of 60-90° C., time of 8-12 hours; the conditions for calcination include: temperature of 300-800° C., time of 1-4 hours.
[0008] In a second aspect, the present invention proposes an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the above-mentioned method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0009] The third aspect of the present invention proposes a method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, comprising: mixing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material described above with ethanol to form a slurry, and coating the slurry on the electrode on the surface of a ceramic tube.
[0010] Preferably, the mass volume ratio of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material to ethanol is 6-12 mg:20 mL.
[0011] The fourth aspect of the present invention proposes a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the above-mentioned method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0012] The Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material and preparation method, hydrogen sensor and preparation method described in the present invention have at least the following beneficial effects:
[0013] (1) The present invention first prepares an Au-loaded ZnO sensitive material with a hierarchical microsphere structure assembled from small-sized nanosheets through a hydrothermal reaction, then reacts the Au-loaded ZnO sensitive material with ZnO under acidic conditions provided by boric acid through ammonium hexafluorostannate to generate SnO2, and further annealing is performed to achieve the diffusion of Sn atoms to form Zn2SnO4, and finally form an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material. The hydrogen sensor prepared using the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material of the present invention has high sensitivity in detecting hydrogen, with the best sensitivity at 240°C, a low operating temperature, and good repeatability and hydrogen selectivity.
[0014] (2) The present invention adopts liquid phase deposition method to prepare Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, which is simple, low-cost, highly repeatable, and suitable for large-scale industrial production;
[0015] (3) Under preferred circumstances, by rationally regulating the content of each substance and the reaction conditions during the preparation of the Au-loaded ZnO sensitive material and the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, the hydrogen sensor prepared by the present invention has a good response between 20 and 300 ppm, and the sensor has good response recovery characteristics and the sensitivity remains stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a scanning electron microscope image of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 of the present invention;
[0017] Figure 2 This is the XRD pattern of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 of the present invention;
[0018] Figure 3 This is a working temperature-sensitivity curve of the hydrogen sensor based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 of the present invention;
[0019] Figure 4a This is a graph showing the repeated response of the hydrogen sensor based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material to 50 ppm hydrogen, prepared in Example 1 of the present invention. Figure 4b Response curve of the hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Invention Example 1 to 20-300 ppm hydrogen at 240°C;
[0020] Figure 5 This is a sensitivity relationship diagram of the hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 of the present invention to carbon monoxide, ethylene, methane and hydrogen. DETAILED DESCRIPTION
[0021] The following describes the specific embodiments of the present invention in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0022] Based on the problems existing in existing hydrogen sensors, the inventors first used a hydrothermal method to add different forming agents to prepare Au-loaded ZnO nanomaterials with different morphologies, such as nanorods, nanosheets, nanotubes, and hierarchical structure microspheres. They then modified them with SnO2 composites and made the above materials into gas sensors for testing. It was found that the hydrogen gas sensing performance of Au-loaded ZnO / Zn2SnO4 / SnO2 composite hierarchical structure microspheres was better. After further research, the following technical solution was finally determined.
[0023] In a first aspect, the present invention provides a method for preparing an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material. The preparation method comprises the following steps: S1, adding the Au-loaded ZnO sensitive material to a mixed solution containing boric acid and ammonium hexafluorostannate for ultrasonic reaction, wherein the Au-loaded ZnO sensitive material reacts with ZnO to form SnO2 through the ammonium hexafluorostannate under acidic conditions provided by boric acid, comprising the following chemical reaction formula: [SnF6] 2- +2H2O→SnO2+4H + +6F-,ZnO+2H + →Zn 2++H2O; S2, the ultrasonic reaction product is cleaned and centrifuged, the collected solid phase product is dried and calcined, and annealed to achieve the diffusion of Sn atoms to form Zn2SnO4, and finally form an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material; the Au-loaded ZnO sensitive material is a hierarchical structure microsphere assembled by nanosheet layers, which has a large specific surface area. Therefore, the Au-loaded ZnO sensitive material is further subjected to liquid phase deposition and annealing to prepare the Au-loaded ZnO / Zn2SnO4 / SnO2 composite material, while basically maintaining the Au-loaded ZnO hierarchical structure microsphere structure with a large specific surface area, which is beneficial to improving the gas sensing performance.
[0024] In a specific embodiment of the preparation method of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material described in the present invention, the preparation method of the Au-loaded ZnO sensitive material is: mixing hexamethylenetetramine, sodium citrate dihydrate, polyvinyl pyrrolidone, hydrated tetrachloroauric acid and water at room temperature to form a first mixed solution, mixing sodium borohydride and water at room temperature to form a second mixed solution, mixing zinc nitrate hexahydrate and water at room temperature to form a third mixed solution, mixing the first mixed solution, the second mixed solution and the third mixed solution at room temperature and transferring them to a stainless steel high-pressure reactor containing a polytetrafluoroethylene liner, and placing them in an oven for hydrothermal reaction; cooling the hydrothermal reaction product to room temperature, washing with deionized water and anhydrous ethanol, centrifuging at a speed of 3000 to 5000 r / min, and drying the solid phase product obtained by centrifugation to obtain the Au-loaded ZnO sensitive material. In a preferred embodiment, the molar ratio of the hydrated tetrachloroauric acid to the zinc nitrate hexahydrate is 1 to 8:100, for example, 1:100, 5:100, 7:100, or 8:100. When the molar ratio of the hydrated tetrachloroauric acid to the zinc nitrate hexahydrate is less than 1:100, the sensitivity of the prepared gas sensor is low. When the molar ratio of the hydrated tetrachloroauric acid to the zinc nitrate hexahydrate is greater than 8:100, the sensitivity of the prepared gas sensor is low. In a more preferred embodiment, the molar ratio of the hydrated tetrachloroauric acid to the zinc nitrate hexahydrate is 5:100, in which case the sensitivity (Ra / Rg) of the prepared gas sensor is even better.
[0025] In a specific embodiment, the usage ratio of hexamethylenetetramine, sodium citrate dihydrate, polyvinyl pyrrolidone and sodium borohydride is 50-60:20-25:1-3:1.
[0026] In a specific embodiment, the conditions for the hydrothermal reaction include: a temperature of 80-150°C and a time of 2-6 hours. For example, the process parameters of the hydrothermal reaction can be selected as: hydrothermal at 95°C for 2 hours, hydrothermal at 120°C for 4 hours, and hydrothermal at 150°C for 1 hour. The hydrothermal reaction product is washed and centrifuged, and the conditions for drying the solid phase product obtained by centrifugation include: a temperature of 60-90°C and a time of 8-12 hours.
[0027] In a specific embodiment of the preparation method of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material of the present invention, the mass ratio of the Au-loaded ZnO sensitive material, boric acid and ammonium hexafluorostannate is 1-2:1:8-10. For example, the mass ratio of the Au-loaded ZnO sensitive material, boric acid and ammonium hexafluorostannate can be 1:1:8, 1.08:1:8.6, 2:1:8, or 2:1:10.
[0028] In a specific embodiment of the preparation method of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material described in the present invention, the conditions for drying the solid phase product obtained by solid-liquid separation include: temperature of 60-90°C, time of 8 to 12 hours; the conditions for calcination include: temperature of 300 to 800°C, time of 1 to 4 hours.
[0029] In a second aspect, the present invention proposes an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the above-mentioned method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0030] The third aspect of the present invention proposes a method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, comprising: mixing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material described above with ethanol to form a slurry, uniformly coating the slurry on the surface of an alumina ceramic tube with a gold electrode, then baking and sintering it under an infrared lamp, welding the sintered insulating ceramic tube to a base, and inserting a heating wire into the inside of the tube, respectively welding the electrode and the heating wire to the electrode on the base to obtain a gas sensitive element, and finally aging the gas sensitive element to obtain a gas sensor.
[0031] In a specific embodiment of the method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to the present invention, the mass volume ratio of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material to ethanol is 6 to 12 mg:20 mL, for example, it can be 6 mg:20 mL, 10 mg:20 mL or 12 mg:20 mL.
[0032] In a specific embodiment, the conditions for baking and sintering under an infrared lamp include: baking time of 10 to 20 minutes, sintering temperature of 300 to 350° C., and sintering time of 1 to 2 hours; the conditions for aging treatment include: temperature of 160 to 280° C., and time of 2 to 7 days.
[0033] The fourth aspect of the present invention proposes a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the above-mentioned method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0034] Unless otherwise specified, the experimental methods or test methods described in the following examples are all conventional methods; the reagents and materials described are all obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0035] Example 1
[0036] A method for preparing an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, the method comprising the following steps:
[0037] Preparation of Au-loaded ZnO sensitive material: 0.4206 g hexamethylenetetramine (C6H 12 N4), 0.1680 g of sodium citrate dihydrate (Na2C6H6O7·2H2O), 0.022 g of polyvinyl pyrrolidone K30 (PVP) and 0.0054 g of hydrated tetrachloroauric acid (HAuCl4·H2O) were dissolved in 162 mL of deionized water and stirred to obtain solution A; 0.0076 g of sodium borohydride (NaBH4) was dissolved in 15 mL of deionized water and stirred to obtain solution B; 0.8924 g of zinc nitrate hexahydrate (Zn(NO3)·6H2O) was dissolved in 1 00mL deionized water, stirred evenly to obtain solution C, wherein the molar ratio of hydrated tetrachloroauric acid to hexahydrate zinc nitrate is 5%; solution A, solution B and solution C are mixed and stirred evenly, transferred to a stainless steel high-pressure reactor containing a polytetrafluoroethylene liner, and placed in an oven for hydrothermal reaction at 95°C for 2h; the hydrothermal product is cooled to room temperature, washed with deionized water and anhydrous ethanol 5 times, and collected by centrifugation at 5000r / min, and the solid phase product collected by centrifugation is dried at 90°C for 10h to obtain the Au-loaded ZnO sensitive material;
[0038] 0.2325 g of boric acid and 2 g of ammonium fluorostannate were dissolved in 50 mL of deionized water and stirred to obtain solution D. 0.25 g of the Au-loaded ZnO sensitive material prepared in Example 1 was added to solution D and ultrasonically reacted for 15 min. The ultrasonic reaction product was then washed 5 times with deionized water and anhydrous ethanol, collected by centrifugation at 5000 r / min, and the solid phase product collected by centrifugation was dried at 90° C. for 10 h. Finally, it was calcined at 700° C. for 2 h to obtain an Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, the structure of which is shown in FIG. Figure 1 Its XRD pattern is shown as Figure 2 shown.
[0039] A method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, the method comprising:
[0040] 0.5 mg of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 was added to 1 mL of ethanol to form a slurry. The slurry was evenly coated on the surface of an alumina ceramic tube with a gold electrode, baked under an infrared lamp for 10 min, and then sintered at 300°C for 2 h.
[0041] The sintered ceramic tube was welded to a six-legged base, and a nickel-chromium heating wire was inserted into the ceramic tube. The gold electrode and the nickel-chromium heating wire were welded to the electrodes on the sensor base respectively. Finally, the tube was placed on an aging table and aged at 280°C for 3 days to obtain a hydrogen sensor A1 based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0042] Example 2
[0043] The method of Example 1 was followed, except that when preparing the Au-loaded ZnO sensitive material, the molar ratio of hydrated tetrachloroauric acid to zinc nitrate hexahydrate was 1%, thereby obtaining a hydrogen sensor A2 based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0044] Example 3
[0045] The method of Example 1 was followed, except that when preparing the Au-loaded ZnO sensitive material, the molar ratio of hydrated tetrachloroauric acid to zinc nitrate hexahydrate was 7%, thereby obtaining a hydrogen sensor A3 based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material.
[0046] Test Case
[0047] The operating temperature and sensitivity of the hydrogen sensor A1 based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 were tested as follows: the hydrogen sensor A1 was placed in a gas-sensitive test box and its sensitivity to 50 ppm hydrogen at different temperatures (200-300°C) was tested (sensitivity = resistance in air / resistance in hydrogen). The results are as follows: Figure 3 As shown by Figure 3 It can be seen that the sensitivity of hydrogen sensor A1 is best at 240℃.
[0048] The detection range and repeatability of the hydrogen sensor A1 based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 were analyzed. The results are shown in Figure 4. Figure 4a is the repeated response curve of the hydrogen sensor A1 to 50ppm hydrogen at the optimal operating temperature of 240°C, and Figure 4b is the dynamic response curve of the hydrogen sensor A1 to 20-300ppm hydrogen. It can be seen from the results of Figure 4 that the hydrogen sensor A1 has good response recovery characteristics and its sensitivity remains stable.
[0049] The selective analysis of the hydrogen sensor A1 based on the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared in Example 1 was carried out. The concentrations of different gases used in the test were 50ppm and 1000ppm respectively. The results are as follows: Figure 5 As shown, from Figure 5 The results show that the hydrogen sensor A1 only shows high sensitivity to hydrogen.
[0050] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for preparing Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, characterized in that: include: The Au-loaded ZnO sensitive material is added to a mixed solution containing boric acid and ammonium hexafluorostannate for ultrasonic reaction, the ultrasonic reaction product is subjected to solid-liquid separation, and the solid phase product obtained by the solid-liquid separation is dried and calcined to obtain the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material; The Au-loaded ZnO sensitive material is a hierarchical structure microsphere assembled from nanosheet layers.
2. The method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 1, characterized in that: The preparation method of the Au-loaded ZnO sensitive material is as follows: Mixing hexamethylenetetramine, sodium citrate dihydrate, polyvinyl pyrrolidone, hydrated tetrachloroauric acid and water to form a first mixed solution, mixing sodium borohydride and water to form a second mixed solution, mixing zinc nitrate hexahydrate and water to form a third mixed solution, mixing the first mixed solution, the second mixed solution and the third mixed solution and performing a hydrothermal reaction; The hydrothermal reaction product is washed and centrifuged, and the solid phase product obtained by centrifugation is dried to obtain the Au-loaded ZnO sensitive material.
3. The method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 1, characterized in that: The mass ratio of the Au-loaded ZnO sensitive material, boric acid and ammonium hexafluorostannate is 1-2:1:8-10.
4. The method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 2, characterized in that: The molar ratio of the hydrated tetrachloroauric acid to the hexahydrated zinc nitrate is 1 to 8:
100.
5. The method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 1, characterized in that: The conditions for drying the solid phase product obtained by solid-liquid separation include: temperature of 60-90°C and time of 8-12h; The calcination conditions include: temperature of 300 to 800° C. and time of 1 to 4 hours.
6. The method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 2, characterized in that: The conditions for the hydrothermal reaction include: a temperature of 80-150° C. and a time of 2-6 hours; the hydrothermal reaction product is washed and centrifuged, and the conditions for drying the solid phase product obtained by centrifugation include: a temperature of 60-90° C. and a time of 8-12 hours.
7. An Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the method for preparing the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to any one of claims 1 to 6.
8. A method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material, characterized in that: include: The Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 7 is mixed with ethanol to form a slurry, and the slurry is coated on the electrode on the surface of the ceramic tube.
9. The method for preparing a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 8, characterized in that: The mass volume ratio of the Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material to ethanol is 6-12 mg:20 mL.
10. A hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material prepared according to the preparation method of a hydrogen sensor based on Au-loaded ZnO / Zn2SnO4 / SnO2 composite sensitive material according to claim 8 or 9.